Molecular cytogenetic characterization of de novo concomitant distal 8p deletion of 8p23.3p23.1 and Xp and Xq deletion of Xp22.13q28 due to an unbalanced X;8 translocation detected by amniocentesis - Chih-Ping Chen; Fang-Yu Hung; Shin-Wen Chen; Fang-Tzu Wu; Yen-Ting Pan; Peih-Shan Wu; Schu-Rern Chern; Chen-Chi Lee; Meng-Shan Lee; Wayseen Wang (Elsevier, 2023)
Objective: We present molecular cytogenetic characterization of de novo concomitant distal 8p deletion of 8p23.3p23.1 and Xp and Xq deletion of Xp22.13q28 due to an unbalanced X;8 translocation detected by amniocentesis. Case report: A 33-year-old primigravid woman underwent amniocentesis at 18 weeks of gestation because of a Down syndrome risk of 1/52 at the first-trimester maternal serum screening calculated from 0.29 multiples of the median (MoM) of pregnancy associated plasma protein-A (PAPP-A), 1.14 MoM of free β-hCG and 0.46 MoM of placental growth factor (PlGF). Amniocentesis revealed a karyotype of 45,X,add(8)(p23.1). The parental karyotypes were normal. Array comparative genomic hybridization (aCGH) analysis on the DNA extracted from cultured amniocytes revealed a 137-Mb deletion of Xp22.13q28 and a 10.53-Mb deletion of 8p23.3p23.1. The karyotype thus was 45,X,der(8)t(X;8)(p22.13;p23.1). Prenatal ultrasound revealed pericardial effusion and skin edema. The pregnancy was subsequently terminated, and a 568-g malformed fetus was delivered with hypertelorism and low-set ears. The cord blood had a karyotype of 45,X,der(8)t(X;8)(p22.13;p23.1). aCGH analysis of the cord blood revealed the result of arr [GRCH37 (hg19)] 8p23.3p23.1 (191,530-10,724,642) × 1.0, arr Xp22.13q28 (18,194,098-155,232,907) × 1.0. Conclusion: aCGH analysis is useful elucidating the genetic nature of an aberrant chromosome with an additional maternal of unknown origin attached to a chromosome terminal region.